Fault location for power grid based on transient travelling wave data fusion via asynchronous voltage measurements. (December 2017) - Rui, Liang; Chenglei, Liu; Nan, Peng; Menghan, Cheng; Fei, Wang
Highlights: An asynchronous fault location method based transient traveling wave data fusion. Refraction and attenuation which affect traveling wave amplitude are considered. A reasonable measuring configuration is suitable for real power grids. The method is validated by simulating IEEE 30-bus test system. Abstract: Considering the complex topology of power grids and their important application, finding an effective fault location algorithm is mandatory. This paper presents a fault location method for power grid based on transient travelling wave data fusion and asynchronous voltage measurements. Firstly, the refraction regularity, attenuation rule and main factors affecting the amplitude of the initial travelling wave are analyzed. Then the modulus maxima of detail coefficients, treated as the feature variables of the initial travelling wave, are extracted via wavelet transform. At last, according to the configuration of the measuring points, fault location scheme based on data fusion theory is proposed. In data level fusion, phase-mode and wavelet transform are carried out in order to obtain the feature variables. In feature level fusion, the fault section is determined through the fault feature variables filtered by the network topology and the artificial neural network is used to fit the relationship between the fault distance and the time difference of arrival between single-terminal aerial-mode and zero-mode voltage. In decision level fusion, the double-terminal fault location algorithm based on the single-ended uploaded data is proposed. The IEEE 30-Bus System is simulated in PSCAD/EMTDC and the fault location algorithm is carried out in MATLAB. The simulation results demonstrate that high-precision fault location could be realized and that practicality and economy are improved without requirements on synchronous sampling.